Magnetoencephalography in Stroke Recovery and Rehabilitation - Paggiaro, Andrea; Birbaumer, Niels; Cavinato, Marianna; Turco, Cristina; Formaggio, Emanuela; Del Felice, Alessandra; Masiero, Stefano; Piccione, Francesco (Frontiers in Neurology, 2016)
Magnetoencephalography (MEG) is a non-invasive neurophysiological technique used to study the cerebral cortex. Currently, MEG is mainly used clinically to localize epileptic foci and eloquent brain areas in order to avoid damage during neurosurgery. MEG might, however, also be of help in monitoring stroke recovery and rehabilitation. This review focuses on experimental use of MEG in Neurorehabilitation. MEG has been employed to detect early modifications in neuroplasticity and connectivity, but there is insufficient evidence as to whether these methods are sensitive enough to be used as a clinical diagnostic test. MEG has also been exploited to derive the relationship between brain activity and movement kinematics for a motor-based brain-computer interface (BCI). In the current body of experimental research MEG appears to be a powerful tool in neurorehabilitation, but it is necessary to produce new data to confirm its clinical utility.